The Impact of COVID-19 on Temple Stays: A Case Study from Koyasan, Japan - Progano, Ricardo (The international journal of religious tourism and pilgrimage, 2021)
The 2020 COVID-19 pandemic had a dramatic impact on worldwide religious tourism, with wide repercussions for both visitors and local stakeholders. However, previous studies on disaster management and tourism do not address the impacts on religious destinations. The viewpoints and experiences of religious stakeholders are seldom studied. Therefore, using a qualitative approach, this research aims to examine the impact of COVID-19 on temple stays by utilising Faulkner’s tourism disaster management framework. The case study of the Buddhist complex of Kōyasan (Wakayama Prefecture, Japan) is taken, where 52 temples offer temple stay services. Two rounds of semi-structured interviews were first carried out with the main local tourism stakeholders. In addition, semi-structured interviews were conducted with Buddhist temples to assess the COVID-19 impacts and the posterior countermeasures taken. Results show that temple stays were negatively affected, losing an important number of visitors since March 2020. In particular, inbound tourism was largely affected, leading to a renewed importance of the domestic market. Novel approaches to funding, teleworking and wellness were reported, as stakeholders explored new avenues towards a post-pandemic scenario. The utilisation of virtual alternatives to physical travel were observed but in a limited form. Also, collaborative networks between lay and religious stakeholders proved to be a vital factor for carrying out disaster management measures and later, tourism initiatives. In particular, the existence of international religious networking for carrying out disaster relief was noted.